ZIP3, a New Splice Variant of the PKC-ζ-interacting Protein Family, Binds to GABAC Receptors, PKC-ζ, and Kvβ2 - Croci, Cristina; Brandstätter, Johann Helmut; Enz, Ralf (Journal of Biological Chemistry, 2003)
The correct targeting of modifying enzymes to ion channels and neurotransmitter receptors represents an important biological mechanism to control neuronal excitability. The recent cloning of protein kinase C-zeta interacting proteins (ZIP1, ZIP2) identified new scaffolds linking the atypical protein kinase PKC-ζ to target proteins. GABAC receptors are composed of three ρ subunits (ρ1-3) that are highly expressed in the retina, where they are clustered at synaptic terminals of bipolar cells. A yeast two-hybrid screen for the GABAC receptor ρ3 subunit identified ZIP3, a new C-terminal splice variant of the ZIP protein family. ZIP3 was ubiquitously expressed in non-neuronal and neuronal tissues, including the retina. The ρ3-binding region of ZIP3 contained a ZZ-zinc finger domain, which interacted with 10 amino acids conserved in ρ1-3 but not in GABAA receptors. Consistently, only ρ1-3 subunits bound to ZIP3. ZIP3 formed dimers with ZIP1-3 and interacted with PKC-ζ and the shaker-type potassium channel subunit Kvβ2. Different domains of ZIP3 interacted with PKC-ζ and the p3 subunit, and simultaneous assembly of ZIP3, PKC-ζ and ρ3 was demonstrated in vitro. Subcellular co-expression of ZIP3 binding partners in the retina supported the proposed protein interactions. Our results indicate the formation of a ternary postsynaptic complex containing PKC-ζ, ZIP3, and GABAC receptors.
UnivIS-Import:2015-04-14:Pub.2003.med.IB.profes_1.zip3an